پرسی كشانه‌وه‌ی هێزه‌ سه‌ربازییه‌كانی ئه‌مریكا له‌ ئه‌فغانستان له‌ ساڵی 2021 (كاریگه‌رییه‌كانی له‌سه‌ر چین و ڕووسیا به‌ نمونه)‌ - الدین, پ.د. سه‌ردار قادر محی; به‌یات, په‌ری رۆكان (Sulaimani Journal for Humanities, 2023)
In 2021 the US ended 20 years of war against Afghanistan. A war that was considered a vital for US national security and position in the world. However, the importance of the war declined throughout 20 years. This study tries to answer questions related to the withdrawal decision, what are the causes of that decision, and how the return of the Taliban to power would affect the national interest and security of both Russia and China as the two main strategic opponents of the US. The study urges that the sudden US withdrawal would affect both Russia and China because the two big countries have to deal with the vacuum that comes as a result of the withdrawal. Hence issues such as terrorism, instability in Afghanistan as well as migration and drug, will determine the policies of both Russia and China toward Afghanistan.